Why Santa Claus is not a god - Barrett, J (Brill, 2008)
Through the lenses of cognitive science of religion, successful god concepts must possess a number of features. God concepts must be (1) counterintuitive, (2) an intentional agent, (3) possessing strategic information, (4) able to act in the human world in detectable ways and (5) capable of motivating behaviors that reinforce belief. That Santa Claus appears to be only inconsistently represented as having all five requisite features Santa has failed to develop a community of true believers and cult. Nevertheless, Santa concepts approximate a successful god concept more closely than other widespread cultural characters such as Mickey Mouse and the Tooth Fairy, in part explaining Santa's relative cultural prominence.